2011
DOI: 10.1190/geo2011-0072.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changing water salinity on complex conductivity spectra of sandstones

Abstract: We analyzed the influence of pore fluid composition on the complex electrical conductivity of three sandstones with differing porosity and permeability. The fluid electrical conductivity (σ w ) of sodium and calcium chloride solutions was gradually increased from 25 mS/m to 2300 mS/m. The expected linear relation between σ w and the real component of electrical conductivity (σ 0 ) of the saturated samples was observed. The imaginary component (σ 0 0 ) exhibits a steeper increase at lower salinities that flatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 28 publications
7
77
0
Order By: Relevance
“…representing the global polarization magnitude (in contrast to σ″ that represents the polarization magnitude at a single frequency) (Weller et al, 2011). Both σ″ and m nor isolate the polarization effects from conduction effects.…”
Section: Debye Decompositionmentioning
confidence: 99%
“…representing the global polarization magnitude (in contrast to σ″ that represents the polarization magnitude at a single frequency) (Weller et al, 2011). Both σ″ and m nor isolate the polarization effects from conduction effects.…”
Section: Debye Decompositionmentioning
confidence: 99%
“…Induced polarization has a long history of use in colloidal chemistry and geophysics, and various petrophysical models have been developed over time to determine the relationship between the in-phase and quadrature conductivities and the texture of the material as well as the electrochemical properties of the mineral water interface [de Lima and Sharma, 1992;Grosse, 2011]. Recent work has focused on the development of a new model based on the polarization of the Stern layer to describe spectral induced polarization of clayey materials with simple supporting electrolytes (e.g., NaCl or KCl) [Revil and Florsch, 2010;Weller et al, 2011;Revil, 2012Revil, , 2013Revil et al, 2013aRevil et al, , 2013c.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative approach, non-invasive geophysical 61 methods can be used in combination with drillings for improved 3D characterization of 62 contaminant plumes. 63 ′ determined from multisalinity resistivity measurements and Furthermore, Weller et al (2013) found that the salinity dependency of the real surface 146 conductivity parallels the salinity dependency of the imaginary surface conductivity, which can be 147 expressed as (Weller et al, 2011;Weller et al, 2015): 148 where * is the complex conductivity, 0 is the DC conductivity, 0 is the intrinsic chargeability, 182 is the relaxation time, is the frequency exponent, is the frequency and is the imaginary 183 unit. Using MCMC (Monte Carlo Markov Chain) analysis, Fiandaca et al (2017a) (Fig.…”
mentioning
confidence: 99%